Community pharmacy services in Vietnam: Consumer demand for nutrition services in pharmacies - Quan, Nguyen Huu Khanh; Giang, Vo Hoang Le (International Journal of Medical and Health Sciences Research, 2025)
Community pharmacies play an important role in providing nutrition services and supporting consumers to receive accurate information and quality products in their healthcare process. This study is one of the few that have examined consumer needs related to nutrition services provided by community pharmacies in Vietnam. The main objective was to identify consumer needs for nutrition services at community pharmacies. Methodology involved a cross-sectional study conducted on 417 respondents who answered questionnaires online and in person in Ho Chi Minh City, Vietnam. The results indicate that almost 100% (417) of consumers usually search the internet first, then seek expert advice to confirm or clarify information. Additionally, 58.2% (243) of consumers are afraid that pharmacists advising on nutritional products in the form of functional foods are often misunderstood as “medicines.” Furthermore, 79.7% (332) of consumers believe that pharmacists are responsible for drugs, not for nutritional advice. The article demonstrates that there is a consumer demand for nutrition services in the healthcare sector. Community pharmacies are at the forefront of providing reliable, responsible, quality products, and nutrition services directly to consumers. Insights into the needs of consumers of nutrition services in community pharmacies are invaluable, and community pharmacists can deliver more valuable nutrition services to primary healthcare. The study recommends that pharmacists working in pharmacies need to update their clinical nutrition knowledge and improve nutrition services to consumers in the context of e-commerce and telehealth services.